Narrativa artesanal e sabedoria popular no norte de Goiás (2017-2019): a arte de produzir conhecimento por meio da oralidade: Artisanal narrative and popular wisdom in northern Goiás (2017-2019): the art of producing knowledge through orality (Revista de História da UEG (REVHIST), 2020)
This paper is result of a research project conducted with male and female narrators between 2017 and 2019, having the northern region of the state of Goiás, Brazil, as a spatial cut. The research was originated from a concern presented in the essay The Narrator, written by Walter Benjamin. The philosopher, faced with modernity, believed to have witnessed the disappearance of the artisanal narrator in the early twentieth century. Through this problem, we provide a survey in order to identify the presence of artisanal narrators in contemporary times. Having identified them, we conducted a field research seeking to understand the influences that these narrators received and that culminated in the artisanal narrative, observing the receptivity and acceptance of those who live in the face of an urban and technological society. From the theoretical framework, Cascudo (1984), Lima (2005), Matos (2014), Brandão (1981) and the field research, we agree with the thesis that the narrators did not disappear, contrary to Benjamin's perspective, but their spaces of sociability so important for narrative communication are diminishing considerably.Keywords: Narrative. Benjamin. Tradition. Modernity.